The Effectiveness of Law Enforcement Against Fraud in the Implementation of the National Health Insurance Program (JKN) - Setyarini, Setyarini; Carolina, Kuntardjo; Ratna, Sugiati; Giri, Respati (Rechtsvinding, 2025)
This study aims to analyze the effectiveness of law enforcement against fraud in the implementation of the National Health Insurance (JKN) program and formulate recommendations to strengthen the legal system and supervision. The method used is normative legal research with a normative juridical approach, including documentation studies of laws and regulations, legal doctrines, and other secondary legal sources. The data analysis technique follows the model of Miles & Huberman (2018) through data reduction, data presentation, and conclusion drawn. The results of the study show that the effectiveness of law enforcement against fraud in the JKN program is still low because the sanctions regulated in regulations, such as the Regulation of the Minister of Health Number 16 of 2019 and Government Regulation Number 28 of 2024 as the implementing regulations of the Health Law number 17 of 2023, are only administrative in nature and do not include strict criminal sanctions, so they do not have a deterrent effect on fraudsters. Weak inter-agency coordination, a lack of optimal supervision and reporting systems, and low public participation in reporting fraud also exacerbate this condition. The analysis also found that the main obstacles came from the lack of legal literacy of participants, weak regulatory supervision, and the lack of optimal implementation of sanctions against violating service providers. To increase the effectiveness of law enforcement, stronger regulatory reforms, strengthening the supervision system, and intensive socialization are needed so that the rights of JKN participants can be optimally protected and public trust in the National Health Insurance program can increase.